Social, Cultural, Economic and Legal Environmental Cost Reporting and Performance of Multinational Companies in Nigeria - Osho, Augustine; Fajuyagbe, Bamikole Samson; Temidayo Olajumoke , Olowolayemo (The Journal of Accounting and Management, 2023)
The study investigated the effect of social, cultural, economic and legal environmental report on performance of multinational firms in Nigeria. This study employed descriptive design method. The data required for this study were secondary in nature and it was sourced from annual financial reports of the sampled listed firms on the Nigerian Exchange Group for period of 5years (2016-2021). The population for this study covered 30 top multinational companies quoted in Nigerian Exchange Group (NGX) as at 30th May, 2022. Five (5) out of 30 listed multinational companies were randomly selected. The study revealed that, social, cultural, economic and legal environmental reporting with attributes of cultural cost; economic cost has an inverse relationship with aggressive profit after tax, whereas social cost and legal cost have positive and significant effect on profit after tax. The study concluded that social, cultural, economic and legal environmental reporting has significant effect on performance of multinational companies in Nigeria, especially, when measured performance in terms of profit after tax. The study therefore recommends that the management of multinational companies need to adequately be aware of the importance of social, cultural, economic and legal environmental reporting, which may improve the performance of the company, and spend extensively in it as this will be a great catalyst for their growth, productivity, and development.